Red land : the illustrated archaeology of Egypt's Eastern Desert - Sidebotham, Steven E. (The American University in Cairo Press, 2008)
"Based on twenty years of archaeological fieldwork conducted in the Eastern Desert, this book reveals the cultural and historical richness of this little known and seldom visited area in Egypt. A range of important archaeological sites dating from Prehistoric to Byzantine times is explored here in text and illustrations. Among these ancient treasures are petroglyphs, cemeteries, fortified wells, gold and emerald mines, hard stone quarries, roads, forts, ports, and temples. With over 280 photographs and artistic reconstructions based on the evidence on the ground, along with the latest research and accounts from ancient sources and modern travelers, the authors lead the reader into the remotest corners of the hauntingly beautiful Eastern Desert to discover the full story of the area's human history."--Jacket